Pengembangan Tolilo Nugget Berbasis Ikan Nila dan Kacang Tolo untuk Balita Underweight Usia 12-59 Bulan - Wianda, Naurah Atiradhia; Rosmana, Dadang; Hapsari, Agustina Indri; Gumilar, Mulus; Putri, Azzahra Nadya (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
Underweight is a condition in which a toddler’s body weight falls below the standard for age. This condition indicates malnutrition and, when prolonged, may lead to stunting. The 2024 Indonesian Nutrition Status Survey (SSGI) reported an underweight prevalence of 16,8 % among toddlers. One government effort to address this issue is the provision of locally sourced Recovery Supplementary Food (PMT). Tolilo Nugget, developed from Nile tilapia and cowpea, which is rich in protein, calcium, and zinc, has the potential to serve as an alternative recovery food for underweight toddlers aged 12 to 59 months. This study aimed to examine the effect of tilapia and cowpea formulations (F1 = 85%:15%, F2 = 75%:25%, and F3 = 65%:35%) on organoleptic properties, energy, protein, fat, carbohydrate, zinc, calcium content, and cost. The research used an experimental design involving 33 semi-trained panelists. The Kruskal Wallis test showed that the formulations did not significantly affect color, aroma, taste, texture, or overall acceptance (p > 0.05). The best formulation was F1. Laboratory analysis showed that per 100 grams, Tolilo Nugget contains 355,75 kilocalories, 10,55 grams of protein, 19,11 grams of fat, 35,39 grams of carbohydrates, 68,55 milligrams of calcium, and 1,37 milligrams of zinc. The cost per serving is IDR 6.611 for children aged 12 to 23 months, IDR 11.019 for children aged 24 to 59 months, and IDR 33.506 per 315-gram package. Therefore, Tolilo Nugget can serve as an alternative locally sourced recovery supplementary food for underweight toddlers, especially those aged 24 to 59 months.